Endovascular treatment of a ruptured portal vein pseudoaneurysm secondary to a large stomach ulcer - John C. DuBois; Aaron M. Rohr; Ian T. Kozlowski; Zachary S. Collins (CVIR Endovascular)
Abstract This case describes the endovascular treatment of a 55-year old female with a ruptured portal vein pseudoaneurysm secondary to a large stomach ulcer resulting in massive active hemorrhage into the adjacent stomach. This patient presented with persistent hypotension secondary to chronic GI blood loss and simultaneous septic shock. After an abrupt drop in blood pressure, the patient arrived in the angiography suite where the ruptured pseudoaneurysm was apparent on portal venogram. Emergent stent assisted coil embolization was performed to stabilize the patient and treat the portal vein pseudoaneurysm. To our knowledge, this case presents the only portal vein pseudoaneurysm secondary to a gastric ulcer. Level of Evidence Level 4, Case-report